The Right to Home Exploring How Space, Culture, and Identity Intersect with Disparities - Hadjiyanni, Tasoulla; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2019)
This book explores how the design characteristics of homes can support or suppress individuals' attempts to create meaning in their lives, which in turn, impacts well-being and delineates the production of health, income, and educational disparities within homes and communities. According to the author, the physical realities of living space-such as how kitchen layouts restrict cooking, the size of social areas limits gatherings with friends, and dining tables represent aspirations-have a salient connection to the beliefs, culture, and happiness of the individuals in the space. The book's purpose is to examine the human capacity to create meaning and to rally home mediators (scholars, educators, design practitioners, policy makes, and advocates) to work toward culturally enriched communities in which everyone can thrive. The volume includes stories from Hmong, Somali, Mexican, Ojibwe, and African American individuals living in Minnesota to show how space intersects with race, gender, citizenship, ability, religion, and ethnicity to posit that social inequalities are partially spacially constructed and are, therefore, malleable.
Preface -- Chapter 1: Introduction - Oikophilia -- Chapter 2: The "and" -- Chapter 3: Hmong Stories - "Only in the house do your dead ancestors live" -- Chapter 4: Somali Stories - "I hope God will not isolate me from my community" -- Chapter 5: Mexican Stories - "I can talk to her and she listens" -- Chapter 6: Ojibwe Stories - "When the traditions are lost, it is like a person who has no identity" -- Chapter 7: African American Stories - "To be self-sufficient and responsible in society" -- Chapter 8: Moving Forward -- Appendix 1 -- Index.
Keywords: Sociology, Urban; Culture -- Study and teaching; Social structure; Equality; Interior architecture; Urban Sociology; Cultural Studies; Social Structure; Interior Architecture